2020
DOI: 10.1590/2177-6709.25.5.23.e1-12.onl
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to quality of life of orthodontists graduated from a public university (1993-2016): A mixed-methods approach

Abstract: Introduction: For dental professionals, including orthodontists, Quality of life (QOL) is a topic of growing concern and could be determined by objective and subjective complex factors. Objective: This study analyzed the factors that influence the QOL of orthodontists graduated between 1993 and 2016 of a public university (Medellín, Colombia). Methods: A mixed-methods study was conducted (cross-sectional survey; 88 participants; 3 focus groups, 21 participants). Quantitative analysis: the research included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…One of the elements that are interesting at first glance is the female participation in the study (81%). This participation is much higher when compared to a similar study conducted on orthodontists at the same university [ 16 ]. During the last decades, there have been feminization processes in many professions, and dentistry is no exception [ 26 ].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…One of the elements that are interesting at first glance is the female participation in the study (81%). This participation is much higher when compared to a similar study conducted on orthodontists at the same university [ 16 ]. During the last decades, there have been feminization processes in many professions, and dentistry is no exception [ 26 ].…”
Section: Discussionmentioning
confidence: 78%
“…A study in Brazil conducted on public sector dentists found that the social domain had the highest scores and the environmental domain had the lowest scores (taking into account the median scores, with scores between 60 and 75) [ 7 ]. One of the most recent studies carried out in Colombia on orthodontists showed a higher score in the psychological dimension and a lower score in the physical dimension (with scores between 57 and 71) [ 16 ]. A study carried out on dentists who teach in Indian hospitals showed that the social relationships dimension obtained the highest scores, and that the dimension related to the environment obtained the lowest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations